EVALUATION OF ELECTRIC AND ELECTRONIC HANDOUT IN AUTOMOTIVE NGEINEERING BY USING FORMATIVE EVALUATION PROCESS - Binta Ustafiano; wawan purwanto (Universitas Sultan Ageng Tirtayasa, 2020)
Currently the automotive sector was equipped with an electronic control system. Thus, students' understanding of electronic systems is crucial. Streamlining the process, in Automotive Engineering study Program in enginering faculty of Universitas Negeri Padang has Electrical and Electronics course. This electrical and electronics course consists of 2 theoretical and 1 practicum credit. Then to expedite the process, a practical module has been provided from the lecturer course team. Science enhancement also influences electronics, so the learning modules require revision of the material, format, and packaging in accordance with the development of field technology applications. In this study focuses on the application of formative evaluation which is expected to provide input for the revision of teaching materials. After the analysis, it can be concluded that the electricity and electronics practicum module as a whole is good, but there are parts that must be improved and added as: material, formulas, examples of data processing, interesting designs, and presented by using e-modules.